2010
DOI: 10.1063/1.3314334
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical verification of microplasma assembly for novel electromagnetic media

Abstract: Microplasmas have a number of potential roles to control propagating electromagnetic waves. This report focuses on novel physics of periodic microplasma assembly for electromagnetic media, which is verified by experimental results and analyzed by numerical methods. Using an assembly composed of microplasmas, novel functions are expected due to its complex dielectric function arising from dielectric and lossy properties. The dielectric property creates photonic band gaps, and the lossy property drastically chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…8) In 2014, split-ring resonators, previously utilized in some of the first metamaterial structures, 4) were used to generate an array of plasmas, which could perhaps be used as a plasma photonic crystal=metamateri-al. 9,10) One may consider the previously mentioned device as an instance of a metamaterial generated by another metamaterial. However, it has also been shown that metamaterials, in this case, for negative refraction, could be made completely of dielectrics, and from this, we drew inspiration.…”
mentioning
confidence: 99%
“…8) In 2014, split-ring resonators, previously utilized in some of the first metamaterial structures, 4) were used to generate an array of plasmas, which could perhaps be used as a plasma photonic crystal=metamateri-al. 9,10) One may consider the previously mentioned device as an instance of a metamaterial generated by another metamaterial. However, it has also been shown that metamaterials, in this case, for negative refraction, could be made completely of dielectrics, and from this, we drew inspiration.…”
mentioning
confidence: 99%
“…The plasma can be obtained by parallel-plate dielectric barrier excitation, multicapillary electrode discharging, cold cathode fluorescent lamp discharging, gas discharging, and so on. Also, heavily doped semiconductor materials can be regarded as plasma materials 25 , 43 – 46 . It is noted that plasma materials have been used for bandgap devices 22 , 25 , PhC waveguides 44 and PhC filters 45 in theory and experiment where characteristic parameters of some plasma materials can be found.…”
Section: Resultsmentioning
confidence: 99%
“…Also, heavily doped semiconductor materials can be regarded as plasma materials 25 , 43 – 46 . It is noted that plasma materials have been used for bandgap devices 22 , 25 , PhC waveguides 44 and PhC filters 45 in theory and experiment where characteristic parameters of some plasma materials can be found. When an external magnetic field is applied, the magnetized plasma becomes anisotropic, dispersive, and dissipative, which depends mainly on the external magnetic fields.…”
Section: Resultsmentioning
confidence: 99%
“…One of them is tunability of the parameters. As we reported previously [6], ε is adjustable to an arbitrary value on the complex ε plane with 0 ) Re( < ε , using variable electron density e n and discharge gas pressure p . Another is a dynamic (time-varying) behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Before the proposal of their concept [9], we performed a series of associated researches on "plasma photonic crystals" [6,7]; in such structures, microplasmas are periodically aligned and band gaps form due to their spatial periodicity, which verifies that plasmas can work as controllers of electromagnetic waves. After these results on the effects of the spatial periodicity, theoretical fundamentals of plasma metamaterials were described in Ref.…”
Section: Introductionmentioning
confidence: 99%